Observations of Gravitational-wave Afterglows. Issue Volume 16:Issue S363(2020) (June 2020) - Corsi, Alessandra
Abstract: GW170817, the merger of two neutron stars witnessed through both its gravitational wave siren and its glow at all wavelengths of light, represents the first multi-messenger detection of a compact binary merger. The association of the GW in-spiral signal from GW170817 with a γ -ray burst, a kilonova, and a non-thermal afterglow spanning all bands of the electromagnetic spectrum, has provided rich constraints on the physics and astrophysics of neutron stars. Starting from the example of GW170817, I briefly summarize recent results on observations of electromagnetic afterglows from gravitational wave triggers. In the light of these results, I highlight some key questions that are yet to be answered after the GW170817 discovery. I conclude by commenting briefly on some opportunities that lie in front of us, as improvements in ground-based gravitational wave detectors' sensitivities will transform a trickle of multi-messenger discoveries into a flood, bringing the field of gravitational wave astronomy from its infancy to its maturity.